The tutor as a bridge to the right to higher education in prison - Decembrotto, Luca; De Rocco, Giulia (Form@re - Open Journal per la formazione in rete, 2025)
Access to university education in Italian prisons has grown steadily over the past decades through the establishment of prison university centres, the Poli Universitari Penitenziari (PUP) (University Penitentiary Centres), enabling an increasing number of incarcerated individuals to pursue academic studies. Within this framework, the role of the university tutor proves strategic in ensuring the effective exercise of the right to education, taking on functions that extend beyond mere didactic support. The paper presents a first analysis of a corpus of ten interviews with PUP delegates and explores the selection processes, practices, and training needs of tutors, highlighting critical issues related to the fragmentation of experiences and the discontinuity of pathways. What emerges is the profile of a bridging figure, able to connect inside and outside, fostering inclusive learning spaces and resilient communities. La figura del tutor come ponte per il diritto allo studio universitario in carcere. L’accesso all’università in carcere in Italia si è consolidato negli ultimi decenni attraverso i Poli Universitari Penitenziari (PUP), che hanno consentito a un numero crescente di persone ristrette di intraprendere percorsi accademici. In questo quadro, la figura del tutor universitario si rivela strategica per garantire l’effettivo esercizio del diritto allo studio, svolgendo funzioni che vanno oltre il mero supporto didattico. Il contributo presenta una prima analisi di un corpus di dieci interviste ai delegati dei PUP e indaga modalità di selezione, pratiche e bisogni formativi dei tutor, evidenziando criticità legate alla frammentarietà delle esperienze e alla discontinuità dei percorsi. Ne emerge il profilo di una figura ponte, capace di connettere dentro e fuori e di generare spazi di apprendimento inclusivi e comunità resilienti.